Evaluation of Activity-Based Budgeting System at Politeknik Unggul LP3M Medan - Nasir, Miftah Faridh (CV. Rayyan Dwi Bharata, 2025)
In the traditional budget system, budgetary activities are assessed in terms of input, i.e. the ability to absorb the budget. If there is a remaining budget because the budget is not fully absorbed, it is considered ineffective. The rest of the budget must be deposited into the state and regional treasury accounts, then the work unit budget is threatened with no increase for the following year or The research method used in this research is descriptive The method using this qualitative approach provides a comprehensive and clear description of the social situation being studied, in this case explaining the changes from the traditional budget system to the activity-based system (performance budget system) The activity-based system at the Superior Polytechnic Education Institute LP3M aims to improve the efficiency, effectiveness and quality of education. By focusing on achieving academic and non-academic performance, using performance indicators such as student grades, graduation rates and parent satisfaction, allocating funds to strategic programs, conducting continuous performance monitoring and evaluation, increasing transparency and accountability in budget management.